(untitled) (American Journal of Technology and Applied Sciences, 2023)
Competitiveness is the capability a country or company has to achieve profitability in the market in relation to its competitors. Competition is a multifaceted economic phenomenon that expresses a complex relationship between all subjects of the market. The article provides an explanation of the role of effective competition in the economy and the improvement of competitive relations.